Pendampingan Kelompok Tani dalam Penerapan Teknik Pembronsongan Buah untuk Pengendalian Hama Kakao - Refki Sanjaya; Soleha Soleha; Abdul Azis; Jamaludin Adimiharja; Dian Latifathul Mar’ah; Tika Leoni Putri; Putri Mariska Fahmi; Irene Zaqyah (PELANTAR PRESS, 2026)
Cocoa production in Indonesia is hampered by pest attacks, namely the fruit-sucking bug Helopeltis spp. And the cocoa pod borer Conopomorpha cramerella. Both pests reduce the quality and quantity of the harvest. This training aims to accompany cocoa farmers in implementing fruit-bagging techniques as an environmentally friendly pest prevention and management. The activity was carried out in Sidomulyo Village, Semaka District, Tanggamus Regency, using extension methods, field demonstrations, and direct practice with farmers. The results showed a notable increase in farmers' understanding of pest identification and their proficiency in applying the cocoa fruit bagging technique. Monitoring of demonstration plots revealed that bagging effectively reduced pest attack intensity from 48% in control plants to 15% in bagged fruits, while the proportion of healthy, harvestable pods increased from 52% to 85%. This technique is considered effective, low-cost, easy to implement, and free from chemical inputs, making it highly suitable for small-scale cocoa farmers. The activity also demonstrated the potential of participatory field-based training in accelerating technology adoption at the grassroots level, thereby supporting the sustainability of cocoa production and the welfare of farming communitie